Two feeding methods based on substrate integrated waveguide for microstrip patch antennas. Issue 5 (1st April 2015) - Mikulasek, Tomas; Lacik, Jaroslav
Abstract : Two feeding methods for microstrip patch antennas (MPAs), namely aperture coupling (AC) and probe feeding (PF), based on a substrate integrated waveguide (SIW) are presented in this study. Exploiting an SIW structure for MPA feeding combines the benefits of both structures. It results in a compact antenna structure retaining advantageous properties of MPAs and having a radiation characteristic non‐effected by spurious radiation that is usually produced by a conventional feeding line. The proposed antenna structures are studied using parametric analyses and their design procedures are presented. The antenna structures are fabricated and verified by measurement at 10 GHz. At the operation frequency, the fabricated AC‐MPA and PF‐MPA with a coax‐to‐SIW transition achieved an impedance bandwidth of 9 and 13.1% and a gain of 8.6 and 9.2 dBi, respectively.